Carbon dioxide-based polycarbonate modified PVC alloy
Patent Information
- Application Number
- CN202611433736.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-16
- Publication Date
- 2026-10-23
AI Technical Summary
[0004]然而,现有技术中关于二氧化碳基聚碳酸酯与PVC共混改性的研究仍较为有限
[0028]本发明合金的维卡软化温度≥82℃拓展了制品应用温度上限;缺口冲击强度≥7.0kJ/m2满足工程应用抗冲击要求;极限氧指数≥28%达到难燃级别,可应用于建筑、交通等防火安全领域;增塑剂迁移率≤1.0wt%从根本上解决因增塑剂析出导致的性能衰减和环境污染问题,使制品具有更长使用寿命和更高卫生安全性。
Abstract
Description
Technical Field
[0001] This invention relates to the field of polymer materials technology, specifically to a carbon dioxide-based polycarbonate-modified PVC alloy. Background Technology
[0002] Polyvinyl chloride (PVC) is one of the world's largest-volume general-purpose plastics, widely used in pipes, profiles, wires and cables, packaging films, and artificial leather due to its low cost, chemical resistance, and excellent electrical insulation. However, PVC itself has poor thermal stability, a narrow processing temperature window (typically between 160–190°C), and is hard and brittle with low notched impact strength in its unmodified state. To obtain flexible products, industrial manufacturers commonly add large amounts of small-molecule plasticizers (such as dioctyl phthalate (DOP) and dioctyl adipate (DOA), typically as high as 30–50 parts by weight). These small-molecule plasticizers are prone to migration, volatilization, and precipitation during use, leading not only to product performance degradation (hardening and brittleness, stickiness) but also potential hazards to human health and the environment. Furthermore, the limiting oxygen index (LOI) of traditional PVC materials is only 23–25, classifying them as flammable materials. Halogenated flame retardants or large amounts of antimony trioxide are usually required to meet flame retardant requirements, further increasing the difficulty of environmental protection and recycling.
[0003] In recent years, with the advancement of the global "carbon neutrality" strategy and increasingly stringent environmental regulations, the development of PVC modification technologies that can reduce or replace small-molecule plasticizers while simultaneously achieving carbon reduction benefits and improved overall performance has become an urgent need in the industry. Carbon dioxide-based polycarbonates are a class of polymeric materials synthesized through copolymerization reactions using carbon dioxide and epoxy compounds as raw materials. Their molecular chains contain a high density of carbonate bonds (—O—CO—O—), exhibiting excellent biodegradability, gas barrier properties, and a certain degree of polarity. Among them, polypropylene carbonate (PPC, a copolymer of carbon dioxide and propylene oxide), polyethylene carbonate (PEC, a copolymer of carbon dioxide and ethylene oxide), and polypropylene carbonate copolymer (PPCP) with the introduction of a third monomer, phthalic anhydride, have shown promising application prospects in packaging films, foaming materials, and fibers. Lianxin Company has previously accumulated numerous patented technologies related to this type of material, covering multiple aspects such as multi-arm structure design, impact-resistant agents, plasticizers, and continuous production processes.
[0004] However, existing research on the blending and modification of carbon dioxide-based polycarbonates (PC) with PVC remains limited. While PPC has been attempted as a long-lasting plasticizer for PVC, its use alone results in insufficient improvement in heat resistance and minimal contribution to flame retardancy. PEC, although possessing the best flexibility and polarity match with PVC, leads to a decrease in the Vicat softening temperature of products when used alone. PPCP, despite having a high glass transition temperature and good char-forming flame retardant potential due to its rigid aromatic ring segments, is too stiff when used alone and requires the addition of other flexible components to achieve a balance of toughness. More importantly, a systematic technical solution has not yet been developed for the blending of these three PCV-based PCs with PVC regarding processing temperature matching, compatibility, and synergistic effects on overall mechanical properties, thus failing to fully leverage the multiple advantages of carbon dioxide-based materials in carbon reduction, temperature resistance, flame retardancy, toughening, and reduced plasticizer migration.
[0005] Therefore, how to develop a PVC blend material with a processing temperature matching PVC (160℃~190℃), easy to blend, capable of significantly reducing the amount of traditional small molecule plasticizers, and simultaneously achieving carbon reduction, improved temperature resistance, enhanced flame retardancy, and toughening effect, based on the existing three types of carbon dioxide-based polycarbonate materials PPC, PEC, and PPCP, through reasonable combination design and process optimization, remains a technical problem that urgently needs to be solved in this field. Summary of the Invention
[0006] The technical problem to be solved by the present invention is to overcome the multiple defects of existing PVC materials and provide a PVC alloy material and its preparation method that can achieve carbon reduction, temperature resistance, flame retardancy, toughening and reduction of plasticizer usage within a processing window of 160~190℃.
[0007] The technical solution adopted by this invention to solve its technical problem is: a carbon dioxide-based polycarbonate modified PVC alloy, characterized in that it is made by blending raw materials comprising the following components: 100 parts by weight of polyvinyl chloride resin; 10-160 parts by weight of carbon dioxide-based polycarbonate, wherein the carbon dioxide-based polycarbonate is selected from one or more of polypropylene carbonate, polyvinyl carbonate, and polypropylene carbonate copolymer, and has a number average molecular weight of 2×10⁻⁶. 4 ~1×10 6 Additives: 0-30 parts by weight; The melt blending temperature of the alloy is 160℃-190℃.
[0008] This invention achieves good compatibility of processing windows by blending carbon dioxide-based polycarbonate with PVC at a matched temperature of 160~190℃, avoiding overheating decomposition or poor plasticization of PVC. Carbon dioxide-based polycarbonate can partially or completely replace traditional small-molecule plasticizers, fundamentally solving the industry pain points of plasticizer migration, volatilization, and precipitation, while also providing carbon reduction benefits and simultaneously improving the heat resistance, flame retardancy, and impact toughness of PVC.
[0009] Specifically, the polypropylene carbonate is a binary copolymer of carbon dioxide and propylene oxide; the polyethylene carbonate is a binary copolymer of carbon dioxide and ethylene oxide; and the polypropylene carbonate copolymer is a terpolymer of carbon dioxide, propylene oxide, and phthalic anhydride. These three carbon dioxide-based polycarbonates have different chain segment structures and glass transition temperatures, contributing to the alloy's differentiated performance. PPC provides flexibility and compatibility; PEC, due to its highest polarity, can form a stronger dipole interaction with PVC to improve blending uniformity; and PPCP, containing rigid aromatic ring segments, can provide a heat-resistant framework and char-forming flame-retardant capabilities. These three can be flexibly selected or combined according to requirements to form a gradient performance control method.
[0010] Preferably, the carbon dioxide-based polycarbonate has a multi-arm structure with the general formula An-C, where A is a polycarbonate segment, n is 2-4, and C is a multi-arm initiator residue. The multi-arm structure allows multiple arms of each molecule to entangle or hydrogen-bond with the PVC molecular chain, forming a physical cross-linked network, significantly improving the alloy's cohesive strength and resistance to plasticizer migration. Experiments show that, at the same molecular weight, the multi-arm structure, compared to the linear structure, can reduce plasticizer migration by 40%-60% and increase notched impact strength by 20%-35%, making it a highly efficient structural modification strategy.
[0011] Preferably, the carbon dioxide-based polycarbonate is a combination of polypropylene carbonate and polypropylene carbonate copolymer, with a weight ratio of 1:0.3~2. The specific ratio of PPC to PPCP can achieve a synergistic effect. PPC provides flexibility and processing fluidity, reducing melt viscosity; PPCP provides a rigid framework and heat-resistant support. Within this weight ratio range, the alloy can simultaneously achieve high notched impact strength (≥7.0 kJ / m). 2 With a temperature of ≥82℃ and a Vicat softening temperature, it achieves an ideal balance of rigidity and toughness, making it particularly suitable for profiles and sheet products.
[0012] Preferably, the carbon dioxide-based polycarbonate is a combination of polyvinyl carbonate and polypropylene carbonate copolymer, with a weight ratio of 1:0.5~3. PEC is the most flexible and polar of the three carbon dioxide-based polycarbonates. When combined with PPCP, it can impart excellent low-temperature flexibility, toughness, and transparency to the alloy while maintaining good heat resistance. The low glass transition temperature (-5~5℃) of PEC can effectively reduce the brittle-ductile transition temperature of the alloy, allowing the product to maintain good impact resistance at low temperatures, making it particularly suitable for frozen food packaging films, medical catheters, and other products.
[0013] Preferably, the carbon dioxide-based polycarbonate is a combination of polypropylene carbonate, polyvinyl carbonate, and a copolymer of polypropylene carbonate, with a weight ratio of 1:0.2~0.8:0.5~2. Using a complete combination of the three carbon dioxide-based polycarbonates, a gradient molecular chain structure can be constructed, ranging from a flexible segment (PEC) to a moderately flexible segment (PPC) and then to a rigid segment (PPCP). PEC provides optimal interfacial wetting and low-temperature toughness, PPC undertakes the main toughening and plasticizing functions, and PPCP provides a heat-resistant framework, flame-retardant charring ability, and anti-migration anchors. The synergistic effect of the three within the above-mentioned ratio range allows the alloy to achieve optimal overall performance: Vicat softening temperature ≥85℃, notched impact strength ≥8.0 kJ / m². 2 Limiting oxygen index ≥30%, plasticizer migration ≤0.8wt%.
[0014] Specifically, the additives include one or more of the following: compatibilizers, heat stabilizers, lubricants, plasticizers, inorganic fillers, and halogen-free flame retardants. The additive system can be flexibly selected and proportioned according to the specific performance requirements and cost budget of the target product. Compatibilizers improve interfacial bonding, heat stabilizers ensure no degradation during processing, lubricants regulate flowability, a small amount of plasticizer finely adjusts softness, inorganic fillers increase rigidity, and halogen-free flame retardants synergistically enhance the flame retardant rating with the char-forming properties of carbon dioxide-based polycarbonate, significantly expanding the adjustable range of alloy properties.
[0015] Preferably, the compatibilizer is a maleic anhydride-grafted acrylate copolymer with a grafting rate of 0.5wt% to 2.0wt% and an amount of 0 to 5 parts by weight.
[0016] Maleic anhydride-grafted acrylate copolymers, used as compatibilizers, exhibit good affinity between their acrylate segments and PVC. The grafted maleic anhydride groups can chemically react with the terminal hydroxyl or carboxyl groups of carbon dioxide-based polycarbonate chains or form strong hydrogen bonds, acting as a "bridge" at the interface between the two phases, significantly reducing interfacial tension and promoting finer particle size of the dispersed phase. Controlling the grafting rate within the range of 0.5–2.0 wt% ensures sufficient reactivity and avoids gelation; preferably 1.5–4 parts by weight can increase tensile strength by 10%–15%.
[0017] Preferably, the heat stabilizer is a calcium-zinc composite stabilizer, with a calcium to zinc molar ratio of 2 to 4:1 and an amount of 0 to 8 parts by weight.
[0018] The calcium-zinc composite stabilizer is free of heavy metals such as lead and cadmium, complying with environmental regulations. Maintaining a calcium-zinc molar ratio of 2-4:1 achieves the optimal balance between initial coloration and long-term thermal stability. Furthermore, the calcium-zinc stabilizer can catalyze the side reactions between carbonate bonds and HCl to some extent, further delaying degradation. A preferred dosage of 3-6 parts by weight ensures that the alloy does not exhibit significant yellowing after continuous processing at 190°C for 30 minutes.
[0019] Preferably, the lubricant is a mixture of calcium stearate and polyethylene wax, with a weight ratio of 1:0.5~2 and an amount of 0~3 parts by weight.
[0020] Calcium stearate, as an internal lubricant, can reduce internal friction in the melt and improve plasticizing efficiency; polyethylene wax, as an external lubricant, can form a lubricating film on the melt and equipment surface, reducing adhesion and frictional heat. When these two are compounded in a weight ratio of 1:0.5 to 2, the residence time of the alloy in the screw can be effectively extended without causing overheating and decomposition, and the surface gloss of the product can be increased by 10% to 20%. The preferred total dosage is 0.8 to 2 parts by weight.
[0021] Preferably, the amount of plasticizer used is 0 to 20 parts by weight, and the plasticizer is selected from one or more of dioctyl phthalate, dioctyl terephthalate, and tributyl acetyl citrate.
[0022] This invention allows for the retention of small amounts of traditional plasticizers, primarily for applications requiring specific product softness. Compared to traditional PVC formulations where plasticizer usage is as high as 30-50 parts by weight, this invention significantly reduces plasticizer usage to 0-20 parts by weight, fundamentally minimizing the risk of plasticizer migration. DOTP or ATBC are preferred plasticizers; the former offers superior migration resistance and electrical insulation, while the latter provides food contact safety.
[0023] Preferably, the amount of the inorganic filler is 0-5 parts by weight, and the inorganic filler is one or more of organic montmorillonite, nano-calcium carbonate or talc.
[0024] Adding appropriate amounts of inorganic fillers can improve the rigidity, dimensional stability, and heat distortion temperature of alloys without significantly sacrificing toughness. The layered structure of organic montmorillonite can form nanoscale dispersions, contributing additional to gas barrier properties and flame retardancy; nano-calcium carbonate is inexpensive, reducing material costs by 5%–10%; talc can improve the surface smoothness of products. A preferred dosage of 1–3 parts by weight can increase the flexural modulus by 15%–25%.
[0025] Preferably, the amount of the halogen-free flame retardant is 0-15 parts by weight, and the halogen-free flame retardant is selected from one or more of aluminum hypophosphite, zinc borate, and magnesium hydroxide.
[0026] Halogen-free flame retardants and the char-forming properties of carbon dioxide-based polycarbonate form a synergistic flame retardant system. Aluminum hypophosphite promotes cross-linking and char formation to create a dense char layer, zinc borate releases water of crystallization and promotes char layer expansion while also suppressing smoke, and magnesium hydroxide decomposes to absorb heat and dilute combustible gases. These three components, combined with the aromatic ring char-forming skeleton of PPCP, can increase the limiting oxygen index of the alloy from around 24 in pure PVC to 28-33, reduce smoke density by 30%-50%, and are completely halogen-free, producing no dioxins or other toxic gases during combustion. A preferred dosage of 5-12 parts by weight can achieve a UL94V-0 flame retardant rating.
[0027] Preferably, the polyvinyl chloride resin is a general-purpose suspension polymer with a degree of polymerization of 800-1300 and a K value of 60-68. Using a general-purpose suspension polymer PVC resin (SG-5 type as the main component, with a K value of 60-65 being preferred) ensures that the alloy has wide availability of raw materials and mature processing compatibility. A degree of polymerization of 800-1300 gives the resin both sufficient mechanical strength and good melt flowability. A K value of 60-68 provides good rheological matching with carbon dioxide-based polycarbonate within a processing window of 160℃-190℃, which is beneficial for uniform dispersion of the dispersed phase.
[0028] The Vicat softening temperature of the alloy of this invention is ≥82℃, which extends the upper limit of the application temperature of the product; the notched impact strength is ≥7.0kJ / m. 2 It meets the impact resistance requirements for engineering applications; with a limiting oxygen index of ≥28%, it reaches the flame-retardant level and can be used in fire safety fields such as construction and transportation; the plasticizer migration rate of ≤1.0wt% fundamentally solves the problems of performance degradation and environmental pollution caused by plasticizer precipitation, giving the products a longer service life and higher hygiene and safety.
[0029] Compared with existing technologies, this invention has the following beneficial effects: This invention uses carbon dioxide-based polycarbonate as the core modifier for PVC, allowing for flexible adjustment of the dosage within a wide range of 10-160 parts by weight. It partially or completely replaces traditional small-molecule plasticizers, fundamentally solving the problems of plasticizer migration, volatilization, and precipitation, while also possessing significant carbon reduction benefits. By selecting one or more of PPC, PEC, and PPCP in combination, and employing a multi-arm structure design, it achieves gradient performance control from flexible to rigid, enabling the alloy to simultaneously obtain a Vicat softening temperature ≥82℃ and a notched impact strength ≥7.0 kJ / m within a processing window of 160℃~190℃. 2 It boasts excellent overall performance, including a limiting oxygen index of ≥28% and a plasticizer migration rate of ≤1.0wt%. Detailed Implementation
[0030] The present invention will now be described in detail through examples. Unless otherwise stated, all raw materials used are commercially available.
[0031] Example 1
[0032] The formulation composition is as follows: Based on 100 parts by weight of polyvinyl chloride resin, SG-5 general-purpose suspension polymerized polyvinyl chloride resin with a degree of polymerization of 1000 and a K value of 65 is selected. The carbon dioxide-based polycarbonate is a combination of PPC and PPCP, where the PPC has a linear structure and a number-average molecular weight of 8 × 10⁻⁶. 4 The glass transition temperature is 35℃, and the dosage is 10 parts by weight; PPCP has a multi-arm structure (n=3) and a number-average molecular weight of 1.5×10⁻⁶. 5 The glass transition temperature is 55℃, and the dosage is 14 parts by weight. The additives include: a compatibilizer made of maleic anhydride-grafted acrylate copolymer with a grafting rate of 1.2 wt% and a melt flow rate of 6 g / 10 min (190℃ / 2.16 kg), with a dosage of 2.5 parts by weight; a heat stabilizer made of calcium-zinc composite stabilizer with a calcium-zinc molar ratio of 3:1, in powder form, with a dosage of 4.5 parts by weight; and an auxiliary heat stabilizer made of epoxidized soybean oil with an epoxy value ≥6.0% and an acid value ≤0.5 mg KOH / g, with a dosage of 3.0 parts by weight. The internal lubricant is calcium stearate, industrial grade, melting point 155℃, used in an amount of 0.6 parts by weight; the external lubricant is polyethylene wax, molecular weight 2500, dropping point 105℃, used in an amount of 0.6 parts by weight; the inorganic filler is organic montmorillonite, modified with hexadecyltrimethylammonium, interlayer spacing 2.8nm, used in an amount of 1.5 parts by weight; the plasticizer is dioctyl terephthalate (DOTP), industrial grade, purity ≥99%, used in an amount of 10 parts by weight.
[0033] The preparation process steps are as follows:
[0034] The first step is the premixing process. An SHR-200L high-speed mixer with a volume of 200L, variable frequency speed control, jacketed electric heating, and water cooling is used. The hot mixing stage begins with the following: 100 parts by weight of polyvinyl chloride resin, 4.5 parts by weight of calcium-zinc composite stabilizer, 0.6 parts by weight of calcium stearate, 0.6 parts by weight of polyethylene wax, and 3.0 parts by weight of epoxidized soybean oil are weighed according to the formula and added sequentially to the high-speed mixer. The mixer is started, and the speed is set to 1200 rpm. The jacket is heated with steam until the material temperature reaches 110-115℃, and the hot mixing time is 7 minutes, allowing the stabilizer and lubricant to fully adsorb onto the surface of the PVC particles. The cold mixing stage then begins: heating is stopped, and the jacket circulating cooling water is switched to an inlet water temperature of 20℃, with the speed reduced to 800 rpm. When the material temperature drops to 85-90℃, 2.5 parts by weight of maleic anhydride-grafted acrylate copolymer, 1.5 parts by weight of organo-modified montmorillonite, and 10 parts by weight of dioctyl terephthalate are added. Continue cold mixing until the material temperature drops below 45°C before discharging. Install a 40-mesh sieve at the discharge port to obtain the PVC premix. Separately, take 10 parts by weight of polypropylene carbonate and 14 parts by weight of polypropylene carbonate copolymer, and dry mix them at room temperature for 4 minutes at 200 rpm in another low-speed mixer to obtain carbon dioxide-based polycarbonate masterbatch. Combine the above PVC premix and carbon dioxide-based polycarbonate masterbatch, and dry mix them at 800 rpm for 3 minutes in a high-speed mixer to obtain the final mixture. The final mixture should not be stored for more than 4 hours to avoid moisture absorption.
[0035] The second step is the melt blending and granulation process. An SHJ-36 co-rotating parallel twin-screw extruder is used, with a screw diameter of 36mm and an L / D ratio of 44:1, equipped with a vacuum exhaust port and a water bath pelletizing system. The screw assembly configuration is as follows: the conveying section uses large-lead conveyor blocks; the melting section uses kneading blocks KB45° / 5 / 36 and KB60° / 4 / 36; the mixing section uses toothed discs and small-lead conveyor blocks; the exhaust section uses reverse threads with a vacuum port; and the homogenization section uses large-lead conveyor blocks. The temperature settings for each zone of the twin-screw extruder are as follows: Zone 1 (feeding section) 160℃, Zone 2 168℃, Zone 3 178℃, Zone 4 186℃, Zone 5 188℃, Zone 6 188℃, Zone 7 186℃, Zone 8 (vacuum inlet) 182℃, Zone 9 183℃, Zone 10 182℃, Zone 11 180℃, Zone 12 178℃, and die head and propellant head 184℃. The process parameters are set as follows: main extruder speed 220 rpm, feeding frequency 28 Hz, corresponding to a production capacity of approximately 20 kg / h, torque maintained at 60%~70%, current 20~23 A, melt pressure 5~6 MPa, vacuum degree -0.07 MPa, and material residence time in the screw 4 min. The total mixture is fed into the twin-screw extruder via a feeder. The material sequentially undergoes conveying, melting, shearing dispersion, vacuum devolatilization, and homogenization before being extruded from the die head. The extruded molten material is cooled in a water bath at 25-30℃ (4m long, 10m / min) and then cut into 3-4mm long pellets by a gantry pelletizer. After being dehydrated in a centrifugal dryer for 30 seconds, the pellets are then dried in a fluidized bed dryer at 60℃ with hot air until the moisture content is ≤0.08%. The final product is carbon dioxide-based polycarbonate modified PVC alloy pellets, which are sealed in aluminum foil composite bags, protected with nitrogen, and stored at room temperature.
[0036] The alloy granules obtained in this embodiment were subjected to performance tests, and the results are as follows: the Vicat softening temperature (B50 method) is 86℃, and the notched impact strength (23℃) is 7.8kJ / m. 2 The tensile strength was 46 MPa, the elongation at break was 120%, the limiting oxygen index was 29%, the plasticizer migration rate (70℃×24h, filter paper pressing method) was 0.7 wt%, the melt flow rate (190℃ / 2.16 kg) was 3.2 g / 10 min, and the Congo red test paper method (190℃×5 min) showed no color change and no HCl release.
[0037] Example 2
[0038] The formulation composition is as follows: Based on 100 parts by weight of polyvinyl chloride resin, SG-5 general-purpose suspension polymerized polyvinyl chloride resin with a degree of polymerization of 800 and a K value of 60 is selected. Carbon dioxide-based polycarbonate is selected from PEC and PPCP, where PEC has a linear structure and a number average molecular weight of 2 × 10⁻⁶. 4Glass transition temperature -5℃, dosage 8 parts by weight; PPCP has a linear structure and a number-average molecular weight of 8×10⁻⁶. 4 The glass transition temperature is 48°C, and the dosage is 24 parts by weight. The additives include: a compatibilizer made of maleic anhydride-grafted acrylate copolymer with a grafting rate of 0.5 wt% and a melt flow rate of 8 g / 10 min (190℃ / 2.16 kg), used in a dosage of 1.5 parts by weight; a heat stabilizer made of calcium-zinc composite stabilizer with a calcium-zinc molar ratio of 2:1, in powder form, used in a dosage of 3 parts by weight; an auxiliary heat stabilizer made of epoxidized soybean oil with an epoxy value ≥6.0% and an acid value ≤0.5 mg KOH / g, used in a dosage of 2 parts by weight; an internal lubricant made of calcium stearate, industrial grade, with a melting point of 155℃, used in a dosage of 0.4 parts by weight; an external lubricant made of polyethylene wax with a molecular weight of 2500 and a dropping point of 105℃, used in a dosage of 0.8 parts by weight; an inorganic filler made of nano-calcium carbonate with a particle size of 80 nm and surface activated treatment, used in a dosage of 3 parts by weight; and a plasticizer made of acetylated tributyl citrate (ATBC), food grade, with a purity ≥99%, used in a dosage of 5 parts by weight.
[0039] The preparation process steps are as follows:
[0040] The first step is the premixing process. An SHR-200L high-speed mixer with a volume of 200L, variable frequency speed control, jacketed electric heating, and water cooling is used. The hot mixing stage begins with the following: 100 parts by weight of polyvinyl chloride resin, 3 parts by weight of calcium-zinc composite stabilizer, 0.4 parts by weight of calcium stearate, 0.8 parts by weight of polyethylene wax, and 2 parts by weight of epoxidized soybean oil are weighed according to the formula and added sequentially to the high-speed mixer. The mixer is started, and the speed is set to 1200 rpm. The jacket is steam-heated until the material temperature reaches 110-115℃, and the hot mixing time is 6 minutes, allowing the stabilizer and lubricant to fully adsorb onto the surface of the PVC particles. The cold mixing stage then begins: heating is stopped, and the jacket circulating cooling water is switched to an inlet water temperature of 20℃, with the speed reduced to 800 rpm. When the material temperature drops to 85-90℃, 1.5 parts by weight of maleic anhydride-grafted acrylate copolymer, 3 parts by weight of nano-calcium carbonate, and 5 parts by weight of tributyl acetylacetonate are added. Continue cold mixing until the material temperature drops below 45°C before discharging. Install a 40-mesh sieve at the discharge port to obtain the PVC premix. Separately, take 8 parts by weight of polyvinyl carbonate and 24 parts by weight of polypropylene carbonate copolymer, and dry mix them at room temperature for 3 minutes at 200 rpm in another low-speed mixer to obtain carbon dioxide-based polycarbonate masterbatch. Combine the above PVC premix and carbon dioxide-based polycarbonate masterbatch, and dry mix them at 800 rpm for 3 minutes in a high-speed mixer to obtain the final mixture. The final mixture should not be stored for more than 4 hours to avoid moisture absorption.
[0041] The second step is the melt blending and granulation process. An SHJ-36 co-rotating parallel twin-screw extruder with a screw diameter of 36mm and an L / D ratio of 44:1 is used, equipped with a vacuum exhaust port and a water bath pelletizing system. The screw configuration is the same as in Example 1. The temperature settings for each zone of the twin screw are as follows: Zone 1 (feeding section) 162℃, Zone 2 170℃, Zone 3 178℃, Zone 4 184℃, Zone 5 186℃, Zone 6 186℃, Zone 7 184℃, Zone 8 (vacuum port) 180℃, Zone 9 181℃, Zone 10 180℃, Zone 11 178℃, Zone 12 176℃, and die head and dies head 182℃. The process parameters are set as follows: main engine speed 200 rpm, feeding frequency 25 Hz, corresponding output of approximately 18 kg / h, torque maintained at 55%~65%, current 18A~22A, melt pressure 4MPa~5MPa, vacuum degree -0.06MPa, and material residence time in the screw 5 min. The total mixture is fed into a twin-screw extruder via a feeder. The material sequentially undergoes conveying, melting, shearing dispersion, vacuum devolatilization, and homogenization before being extruded from the die head. The extruded molten strip is cooled in a water bath at 25~30℃ (water tank length 4m, traction speed 9m / min) and then cut into 3~4mm length pellets by a gantry pelletizer. After dehydration in a centrifugal dryer for 30s, the pellets are sent to a fluidized bed dryer and dried with hot air at 60℃ until the moisture content is ≤0.08%. The final product is carbon dioxide-based polycarbonate modified PVC alloy pellets, which are sealed in aluminum foil composite bags, protected with nitrogen, and stored at room temperature.
[0042] The alloy granules obtained in this embodiment were subjected to performance tests, and the results are as follows: the Vicat softening temperature (B50 method) is 84℃, and the notched impact strength (23℃) is 7.2kJ / m. 2 The tensile strength was 43 MPa, the elongation at break was 135%, the limiting oxygen index was 30%, the plasticizer migration rate (70℃×24h, filter paper pressing method) was 0.6 wt%, the melt flow rate (190℃ / 2.16 kg) was 4.1 g / 10 min, and the Congo red test paper method (190℃×5 min) showed no color change and no HCl release. The carbon dioxide-based polycarbonate modified PVC alloy prepared in this embodiment uses a combination of PEC and PPCP, fully utilizing the high polarity and low-temperature flexibility of PEC with the heat-resistant skeleton and char-forming flame-retardant ability of PPCP, achieving good blending results within a relatively low processing temperature window.
[0043] Example 3
[0044] The formulation composition is as follows: Based on 100 parts by weight of polyvinyl chloride resin, SG-5 general-purpose suspension polymerized polyvinyl chloride resin with a degree of polymerization of 1300 and a K value of 68 is selected. The carbon dioxide-based polycarbonate is a combination of PPC, PEC, and PPCP, where PPC has a linear structure and a number-average molecular weight of 6 × 10⁻⁶.5 The glass transition temperature is 38℃, and the dosage is 20 parts by weight; PEC has a multi-arm structure (n=4) and a number-average molecular weight of 1×10⁻⁶. 6 The glass transition temperature is 5℃, and the dosage is 16 parts by weight; PPCP has a multi-arm structure (n=3) and a number-average molecular weight of 8×10⁻⁶. 5 The glass transition temperature is 60℃, and the dosage is 40 parts by weight. The weight ratio of the three components is 1:0.8:2. The additives include: a compatibilizer made of maleic anhydride-grafted acrylate copolymer with a grafting rate of 2.0wt% and a melt flow rate of 5g / 10min (190℃ / 2.16kg), with a dosage of 4 parts by weight; a heat stabilizer made of calcium-zinc composite stabilizer with a calcium-zinc molar ratio of 4:1, in powder form, with a dosage of 6 parts by weight; an auxiliary heat stabilizer made of epoxidized soybean oil with an epoxy value ≥6.0% and an acid value ≤0.5mgKOH / g, with a dosage of 4 parts by weight; and an internal lubricant made of calcium stearate, industrial grade, with a melting point of 1. 55℃, dosage is 1.0 part by weight; external lubricant is polyethylene wax, molecular weight 2500, dropping point 105℃, dosage is 0.5 parts by weight; inorganic filler is organic montmorillonite, modified with hexadecyltrimethylammonium, interlayer spacing 2.8nm, dosage is 2 parts by weight; halogen-free flame retardant is a combination of aluminum hypophosphite and zinc borate, with a weight ratio of 2:1, total dosage is 12 parts by weight; plasticizer is dioctyl terephthalate (DOTP), industrial grade, purity ≥99%, dosage is 15 parts by weight.
[0045] The preparation process steps are as follows:
[0046] The first step is the premixing process. An SHR-200L high-speed mixer with a volume of 200L, variable frequency speed control, jacketed electric heating, and water cooling is used. The hot mixing stage begins with the following: 100 parts by weight of polyvinyl chloride resin, 6 parts by weight of calcium-zinc composite stabilizer, 1.0 part by weight of calcium stearate, 0.5 parts by weight of polyethylene wax, and 4 parts by weight of epoxidized soybean oil are weighed according to the formula and added sequentially to the high-speed mixer. The mixer is started, and the speed is set to 1200 rpm. The jacket is steam-heated until the material temperature reaches 110-115℃, and the hot mixing time is 8 minutes, allowing the stabilizer and lubricant to fully adsorb onto the surface of the PVC particles. The cold mixing stage then begins: heating is stopped, and the jacket circulating cooling water is switched to an inlet water temperature of 20℃, with the speed reduced to 800 rpm. When the material temperature drops to 85-90℃, 4 parts by weight of maleic anhydride-grafted acrylate copolymer, 2 parts by weight of organo-modified montmorillonite, 8 parts by weight of aluminum hypophosphite, 4 parts by weight of zinc borate, and 15 parts by weight of dioctyl terephthalate are added. Continue cold mixing until the material temperature drops below 45°C before discharging. Install a 40-mesh sieve at the discharge port to obtain the PVC premix. Separately, take 20 parts by weight of polypropylene carbonate, 16 parts by weight of polyethylene carbonate, and 40 parts by weight of the polypropylene carbonate copolymer. Dry mix them at room temperature for 5 minutes at 200 rpm in another low-speed mixer to obtain carbon dioxide-based polycarbonate masterbatch. Combine the above PVC premix and carbon dioxide-based polycarbonate masterbatch, and dry mix them at 800 rpm for 3 minutes in a high-speed mixer to obtain the final mixture. The final mixture should not be stored for more than 4 hours to avoid moisture absorption.
[0047] The second step is the melt blending and granulation process. An SHJ-36 co-rotating parallel twin-screw extruder with a screw diameter of 36mm and an L / D ratio of 44:1 is used, equipped with a vacuum exhaust port and a water bath pelletizing system. The screw configuration is the same as in Example 1. The temperature settings for each zone of the twin screw are as follows: Zone 1 (feeding section) 160℃, Zone 2 168℃, Zone 3 178℃, Zone 4 186℃, Zone 5 190℃, Zone 6 190℃, Zone 7 188℃, Zone 8 (vacuum port) 185℃, Zone 9 186℃, Zone 10 185℃, Zone 11 183℃, Zone 12 180℃, and the die head and prong head 188℃. The process parameters are set as follows: main engine speed 250 rpm, feeding frequency 30 Hz, corresponding output of approximately 22 kg / h, torque maintained at 70%~80%, current 23A~26A, melt pressure 6MPa~7MPa, vacuum degree -0.08MPa, and material residence time in the screw 3 min. The total mixture is fed into a twin-screw extruder via a feeder. The material sequentially undergoes conveying, melting, shearing dispersion, vacuum devolatilization, and homogenization before being extruded from the die head. The extruded molten strip is cooled in a water bath at 25~30℃ (water tank length 4m, traction speed 12m / min) and then cut into 3mm~4mm length pellets by a gantry pelletizer. After dehydration in a centrifugal dryer for 30s, the pellets are sent to a fluidized bed dryer and dried with hot air at 60℃ until the moisture content is ≤0.08%. The final product is carbon dioxide-based polycarbonate modified PVC alloy pellets, which are sealed in aluminum foil composite bags, protected with nitrogen, and stored at room temperature.
[0048] The alloy granules obtained in this embodiment were subjected to performance tests, and the results are as follows: the Vicat softening temperature (B50 method) is 90℃, and the notched impact strength (23℃) is 8.5kJ / m. 2 The tensile strength was 48 MPa, the elongation at break was 95%, the limiting oxygen index was 33%, the plasticizer migration rate (70℃×24h, filter paper pressing method) was 0.5 wt%, the melt flow rate (190℃ / 2.16kg) was 2.5 g / 10 min, and the Congo red test paper method (190℃×5 min) showed no color change and no HCl release.
[0049] The carbon dioxide-based polycarbonate-modified PVC alloy prepared in this embodiment employs a complete combination scheme of three carbon dioxide-based polycarbonates: PPC, PEC, and PPCP, constructing a fully gradient molecular chain structure from flexible to rigid segments. The multi-arm structure design reduces the plasticizer migration rate to 0.5 wt%, and the synergistic effect of the halogen-free flame retardant achieves a limiting oxygen index of 33%, realizing a UL94V-0 flame retardant rating.
[0050] Example 4
[0051] The formulation composition is as follows: Based on 100 parts by weight of polyvinyl chloride resin, SG-5 general-purpose suspension polymerized polyvinyl chloride resin with a degree of polymerization of 1000 and a K value of 65 is selected. The carbon dioxide-based polycarbonate is a single component of polypropylene carbonate (PPC), which has a linear structure and a number average molecular weight of 2 × 10⁻⁶. 5 The glass transition temperature is 32℃, and the dosage is 60 parts by weight. The additives include: a compatibilizer made of maleic anhydride-grafted acrylate copolymer with a grafting rate of 1.5 wt% and a melt flow rate of 6 g / 10 min (190℃ / 2.16 kg), with a dosage of 5 parts by weight; a heat stabilizer made of calcium-zinc composite stabilizer with a calcium-zinc molar ratio of 3:1, in powder form, with a dosage of 8 parts by weight; an auxiliary heat stabilizer made of epoxidized soybean oil with an epoxy value ≥6.0% and an acid value ≤0.5 mg KOH / g, with a dosage of 5 parts by weight; and an internal lubricant. Calcium stearate, industrial grade, melting point 155℃, is used in a dosage of 1.5 parts by weight; polyethylene wax, molecular weight 2500, dropping point 105℃, is used in a dosage of 1.5 parts by weight; talc powder, 1250 mesh particle size, with silane surface treatment, is used in a dosage of 5 parts by weight; magnesium hydroxide, silanized, with 2μm particle size, is used as the halogen-free flame retardant; no traditional small molecule plasticizers are used, and the plasticizer dosage is 0 parts by weight.
[0052] The preparation process steps are as follows:
[0053] The first step is the premixing process. An SHR-200L high-speed mixer with a volume of 200L, variable frequency speed control, jacket electric heating, and water cooling is used. The hot mixing stage begins with the following: 100 parts by weight of polyvinyl chloride resin, 8 parts by weight of calcium-zinc composite stabilizer, 1.5 parts by weight of calcium stearate, 1.5 parts by weight of polyethylene wax, and 5 parts by weight of epoxidized soybean oil are weighed according to the formula and added sequentially to the high-speed mixer. The mixer is started, and the speed is set to 1200 rpm. The jacket is steam-heated until the material temperature reaches 110-115℃, and the hot mixing time is 8 minutes, allowing the stabilizer and lubricant to fully adsorb onto the surface of the PVC particles. The cold mixing stage then begins: heating is stopped, and the jacket circulating cooling water is switched to an inlet water temperature of 20℃. The speed is reduced to 800 rpm. When the material temperature drops to 85-90℃, 5 parts by weight of maleic anhydride-grafted acrylate copolymer, 5 parts by weight of talc, and 15 parts by weight of magnesium hydroxide are added. Continue cold mixing until the material temperature drops below 45°C before discharging. Install a 40-mesh sieve at the discharge port to obtain the PVC premix. Separately, take 60 parts by weight of polypropylene carbonate and dry mix it at room temperature for 2 minutes at 200 rpm in a low-speed mixer to obtain carbon dioxide-based polycarbonate masterbatch. Combine the above PVC premix and carbon dioxide-based polycarbonate masterbatch, and dry mix them at 800 rpm for 3 minutes in a high-speed mixer to obtain the final mixture. The final mixture should not be stored for more than 4 hours to avoid moisture absorption.
[0054] The second step is the melt blending and granulation process. An SHJ-36 co-rotating parallel twin-screw extruder with a screw diameter of 36mm and an L / D ratio of 44:1 is used, equipped with a vacuum exhaust port and a water bath pelletizing system. The screw configuration is the same as in Example 1. The temperature settings for each zone of the twin screw are as follows: Zone 1 (feeding section) 155℃, Zone 2 163℃, Zone 3 172℃, Zone 4 180℃, Zone 5 185℃, Zone 6 185℃, Zone 7 183℃, Zone 8 (vacuum port) 180℃, Zone 9 181℃, Zone 10 180℃, Zone 11 178℃, Zone 12 176℃, and the die head and prong head 180℃. The process parameters are set as follows: main engine speed 180 rpm, feeding frequency 22 Hz, corresponding to an output of approximately 16 kg / h, torque maintained at 50%~60%, current 16A~20A, melt pressure 3MPa~4MPa, vacuum degree -0.06MPa, and material residence time in the screw 5 min. The total mixture is fed into a twin-screw extruder via a feeder. The material sequentially undergoes conveying, melting, shearing dispersion, vacuum devolatilization, and homogenization before being extruded from the die head. The extruded molten strip is cooled in a water bath at 25℃~30℃ (water tank length 4m, traction speed 8m / min) and then cut into 3mm~4mm length pellets by a gantry pelletizer. After dehydration in a centrifugal dryer for 30s, the pellets are sent to a fluidized bed dryer and dried with hot air at 60℃ until the moisture content is ≤0.08%. The final product is carbon dioxide-based polycarbonate modified PVC alloy pellets, which are sealed in aluminum foil composite bags, protected with nitrogen, and stored at room temperature.
[0055] The alloy granules obtained in this embodiment were subjected to performance tests, and the results are as follows: the Vicat softening temperature (B50 method) is 82℃, and the notched impact strength (23℃) is 7.0 kJ / m. 2 The tensile strength was 41 MPa, the elongation at break was 150%, the limiting oxygen index was 31%, the plasticizer migration rate (70℃×24h, filter paper pressing method) was 0.3 wt%, the melt flow rate (190℃ / 2.16kg) was 5.0 g / 10 min, and the Congo red test paper method (190℃×5 min) showed no color change and no HCl release.
[0056] Example 5
[0057] The formulation composition is as follows: Based on 100 parts by weight of polyvinyl chloride resin, SG-5 general-purpose suspension polymerized polyvinyl chloride resin with a degree of polymerization of 1000 and a K value of 65 is selected. The carbon dioxide-based polycarbonate is a combination of PPC and PPCP in a weight ratio of 1:1, wherein the PPC has a linear structure and a number average molecular weight of 5 × 10⁻⁶. 4 The glass transition temperature is 30℃, and the dosage is 15 parts by weight; PPCP has a multi-arm structure (n=3) and a number-average molecular weight of 2×10⁻⁶. 5The glass transition temperature is 58℃, and the dosage is 15 parts by weight. The additives include: a compatibilizer made of maleic anhydride-grafted acrylate copolymer with a grafting rate of 1.2 wt% and a melt flow rate of 6 g / 10 min (190℃ / 2.16 kg), used in 3 parts by weight; a heat stabilizer made of calcium-zinc composite stabilizer with a calcium-zinc molar ratio of 3:1, in powder form, used in 4.5 parts by weight; an auxiliary heat stabilizer made of epoxidized soybean oil with an epoxy value ≥6.0% and an acid value ≤0.5 mg KOH / g, used in 3 parts by weight; and an internal lubricant made of hard... Calcium fatty acid, industrial grade, melting point 155℃, dosage 0.6 parts by weight; external lubricant is polyethylene wax, molecular weight 2500, dropping point 105℃, dosage 0.6 parts by weight, the weight ratio of the two is 1:1, total dosage 1.2 parts by weight; inorganic filler is organic montmorillonite, modified with hexadecyltrimethylammonium, interlayer spacing 2.8nm, dosage 2 parts by weight; plasticizer is dioctyl terephthalate (DOTP), industrial grade, purity ≥99%, dosage 10 parts by weight.
[0058] The preparation process steps are as follows:
[0059] The first step is the premixing process. An SHR-200L high-speed mixer with a volume of 200L, variable frequency speed control, jacketed electric heating, and water cooling is used. The hot mixing stage begins with the following: 100 parts by weight of polyvinyl chloride resin, 4.5 parts by weight of calcium-zinc composite stabilizer, 0.6 parts by weight of calcium stearate, 0.6 parts by weight of polyethylene wax, and 3 parts by weight of epoxidized soybean oil are weighed according to the formula and added sequentially to the high-speed mixer. The mixer is started, and the speed is set to 1200 rpm. The jacket is steam-heated until the material temperature reaches 110℃~115℃, and the hot mixing time is 7 minutes, allowing the stabilizer and lubricant to fully adsorb onto the surface of the PVC particles. The cold mixing stage then begins: heating is stopped, and the jacket circulating cooling water is switched to an inlet water temperature of 20℃, with the speed reduced to 800 rpm. When the material temperature drops to 85℃~90℃, 3 parts by weight of maleic anhydride-grafted acrylate copolymer, 2 parts by weight of organo-modified montmorillonite, and 10 parts by weight of dioctyl terephthalate are added. Continue cold mixing until the material temperature drops below 45°C before discharging. Install a 40-mesh sieve at the discharge port to obtain the PVC premix. Separately, take 15 parts by weight of polypropylene carbonate and 15 parts by weight of polypropylene carbonate copolymer, and dry mix them at room temperature for 4 minutes at 200 rpm in another low-speed mixer to obtain carbon dioxide-based polycarbonate masterbatch. Combine the above PVC premix and carbon dioxide-based polycarbonate masterbatch, and dry mix them at 800 rpm for 3 minutes in a high-speed mixer to obtain the final mixture. The final mixture should not be stored for more than 4 hours to avoid moisture absorption.
[0060] The second step is the melt blending and granulation process. An SHJ-36 co-rotating parallel twin-screw extruder is used, with a screw diameter of 36mm and an L / D ratio of 44:1, equipped with a vacuum exhaust port and a water bath pelletizing system. The screw assembly configuration is as follows: the conveying section uses large-lead conveyor blocks; the melting section uses kneading blocks KB45° / 5 / 36 and KB60° / 4 / 36; the mixing section uses toothed discs and small-lead conveyor blocks; the exhaust section uses reverse threads with a vacuum port; and the homogenization section uses large-lead conveyor blocks. The temperature settings for each zone of the twin-screw extruder strictly follow the optimized temperature curves specified in the instruction manual: Zone 1 (feeding section) 160℃, Zone 2 168℃, Zone 3 178℃, Zone 4 186℃, Zone 5 188℃, Zone 6 188℃, Zone 7 186℃, Zone 8 (vacuum inlet) 182℃, Zone 9 183℃, Zone 10 182℃, Zone 11 180℃, Zone 12 178℃, die head and prong head 184℃, with a maximum temperature of 188℃ throughout the entire process, not exceeding the 190℃ red line. The process parameters are set as follows: main extruder speed 220rpm; feeding frequency 28Hz, corresponding to a production capacity of approximately 20kg / h; torque maintained at 60%~70%, current 20A~23A; melt pressure 5MPa~6MPa; vacuum degree -0.07MPa; material residence time in the screw 4min. The total mixture is fed into a twin-screw extruder via a feeder. The material undergoes sequential conveying, melting, shearing dispersion, vacuum devolatilization, and homogenization before being extruded from the die head. The extruded molten strip is cooled in a water bath at 25℃~30℃ (4m long, 10m / min), then fed into a gantry pelletizer to be cut into 3mm~4mm length pellets. The pellets are then dehydrated in a centrifugal dryer for 30s and then sent to a fluidized bed dryer to be dried with hot air at 60℃ until the moisture content is ≤0.08%. The final product is carbon dioxide-based polycarbonate modified PVC alloy pellets, which are sealed in aluminum foil composite bags, protected with nitrogen, and stored at room temperature.
[0061] The alloy granules obtained in this embodiment were subjected to performance tests, and the results are as follows: the Vicat softening temperature (B50 method) is 87℃, and the notched impact strength (23℃) is 8.0 kJ / m. 2 The tensile strength was 47 MPa, the elongation at break was 115%, the limiting oxygen index was 29%, the plasticizer migration rate (70℃×24h, filter paper pressing method) was 0.6 wt%, the melt flow rate (190℃ / 2.16 kg) was 3.0 g / 10 min, and the Congo red test paper method (190℃×5 min) showed no color change and no HCl release.
[0062] Example 6
[0063] The formulation composition is as follows: Based on 100 parts by weight of polyvinyl chloride resin, SG-5 general-purpose suspension polymerized polyvinyl chloride resin with a degree of polymerization of 1000 and a K value of 65 is selected. The carbon dioxide-based polycarbonate is a combination of PEC and PPCP in a weight ratio of 1:2, wherein the PEC has a multi-arm structure (n=3) and a number-average molecular weight of 4×10⁻⁶. 4 The glass transition temperature is 0℃, and the dosage is 10 parts by weight; PPCP has a multi-arm structure (n=4) and a number-average molecular weight of 3×10⁻⁶. 5 The glass transition temperature is 62℃, and the dosage is 20 parts by weight. The additives include: a compatibilizer made of maleic anhydride-grafted acrylate copolymer with a grafting rate of 1.5 wt% and a melt flow rate of 6 g / 10 min (190℃ / 2.16 kg), with a dosage of 3.5 parts by weight; a heat stabilizer made of calcium-zinc composite stabilizer with a calcium-zinc molar ratio of 3.5:1, in powder form, with a dosage of 5 parts by weight; an auxiliary heat stabilizer made of epoxidized soybean oil with an epoxy value ≥6.0% and an acid value ≤0.5 mg KOH / g, with a dosage of 3.5 parts by weight; and an internal lubricant made of calcium stearate, industrial grade, melt... The drop point is 155℃, and the dosage is 0.5 parts by weight; the external lubricant is polyethylene wax with a molecular weight of 2500 and a dropping point of 105℃, and the dosage is 1.0 parts by weight. The weight ratio of the two is 1:2, and the total dosage is 1.5 parts by weight; the inorganic filler is organic montmorillonite modified with hexadecyltrimethylammonium, with an interlayer spacing of 2.8nm, and the dosage is 2.5 parts by weight; the halogen-free flame retardant is aluminum hypophosphite, and the dosage is 8 parts by weight; the plasticizer is acetylacetic tributyl citrate (ATBC), food grade, with a purity of ≥99%, and the dosage is 8 parts by weight.
[0064] The preparation process steps are as follows:
[0065] The first step is the premixing process. An SHR-200L high-speed mixer with a volume of 200L, variable frequency speed control, jacketed electric heating, and water cooling is used. The hot mixing stage begins with the following: 100 parts by weight of polyvinyl chloride resin, 5 parts by weight of calcium-zinc composite stabilizer, 0.5 parts by weight of calcium stearate, 1.0 part by weight of polyethylene wax, and 3.5 parts by weight of epoxidized soybean oil are weighed according to the formula and added sequentially to the high-speed mixer. The mixer is started, and the speed is set to 1200 rpm. The jacket is steam-heated until the material temperature reaches 110℃~115℃, and the hot mixing time is 7 minutes, allowing the stabilizer and lubricant to fully adsorb onto the surface of the PVC particles. The cold mixing stage then begins: heating is stopped, and the jacket circulating cooling water is switched to an inlet water temperature of 20℃, with the speed reduced to 800 rpm. When the material temperature drops to 85℃~90℃, 3.5 parts by weight of maleic anhydride-grafted acrylate copolymer, 2.5 parts by weight of organo-modified montmorillonite, 8 parts by weight of aluminum hypophosphite, and 8 parts by weight of tributyl acetylacetonate are added. Continue cold mixing until the material temperature drops below 45°C before discharging. Install a 40-mesh sieve at the discharge port to obtain the PVC premix. Separately, take 10 parts by weight of polyvinyl carbonate and 20 parts by weight of polypropylene carbonate copolymer, and dry mix them at room temperature for 4 minutes at 200 rpm in another low-speed mixer to obtain carbon dioxide-based polycarbonate masterbatch. Combine the above PVC premix and carbon dioxide-based polycarbonate masterbatch, and dry mix them at 800 rpm for 3 minutes in a high-speed mixer to obtain the final mixture. The final mixture should not be stored for more than 4 hours to avoid moisture absorption.
[0066] The second step is the melt blending and granulation process. An SHJ-36 co-rotating parallel twin-screw extruder is used, with a screw diameter of 36mm and an L / D ratio of 44:1, equipped with a vacuum exhaust port and a water bath pelletizing system. The screw configuration is the same as in Example 5. The temperature settings for each zone of the twin screw are as follows: Zone 1 (feeding section) 160℃, Zone 2 168℃, Zone 3 178℃, Zone 4 186℃, Zone 5 188℃, Zone 6 188℃, Zone 7 186℃, Zone 8 (vacuum port) 182℃, Zone 9 183℃, Zone 10 182℃, Zone 11 180℃, Zone 12 178℃, and the die head and end cap 184℃. The highest temperature throughout the process is 188℃, not exceeding the red line of 190℃. The process parameters are set as follows: main machine speed 230 rpm; feeding frequency 28 Hz, corresponding to an output of approximately 20 kg / h; torque maintained at 63%~73%, current 21A~24A; melt pressure 5MPa~6MPa; vacuum degree -0.07MPa; material residence time in the screw 4 min. The total mixture is fed into a twin-screw extruder via a feeder. The material sequentially undergoes conveying, melting, shearing dispersion, vacuum devolatilization, and homogenization before being extruded from the die head. The extruded molten strip is cooled in a water bath at a temperature of 25℃~30℃, with a water tank length of 4m and a traction speed of 10m / min. It then enters a gantry pelletizer to be cut into pellets of 3mm~4mm in length. After being dehydrated in a centrifugal dryer for 30s, the pellets are sent to a fluidized bed dryer and dried with hot air at 60℃ until the moisture content is ≤0.08%. Finally, carbon dioxide-based polycarbonate modified PVC alloy pellets are obtained, which are sealed in aluminum foil composite bags, protected with nitrogen, and stored at room temperature.
[0067] The alloy granules obtained in this embodiment were subjected to performance tests, and the results are as follows: the Vicat softening temperature (B50 method) is 88℃, and the notched impact strength (23℃) is 7.6kJ / m. 2 The tensile strength was 45 MPa, the elongation at break was 128%, the limiting oxygen index was 31%, the plasticizer migration rate (70℃×24h, filter paper pressing method) was 0.5 wt%, the melt flow rate (190℃ / 2.16kg) was 3.5 g / 10 min, and the Congo red test paper method (190℃×5 min) showed no color change and no HCl release.
[0068] Example 7
[0069] The formulation composition is as follows: Based on 100 parts by weight of polyvinyl chloride resin, SG-5 general-purpose suspension polymerized polyvinyl chloride resin with a degree of polymerization of 1000 and a K value of 65 is selected. The carbon dioxide-based polycarbonate is a combination of PPC, PEC, and PPCP in a weight ratio of 1:0.5:1.5, where PPC has a multi-arm structure (n=3) and a number-average molecular weight of 1×10⁻⁶. 5 The glass transition temperature is 34℃, and the dosage is 12 parts by weight; PEC has a linear structure and a number-average molecular weight of 3×10⁻⁶.4 Glass transition temperature -2℃, dosage 6 parts by weight; PPCP has a multi-arm structure (n=3) and a number-average molecular weight of 4×10⁻⁶. 5 The glass transition temperature is 60℃, and the dosage is 18 parts by weight. The additives include: a compatibilizer made of maleic anhydride-grafted acrylate copolymer with a grafting rate of 1.8 wt% and a melt flow rate of 6 g / 10 min (190℃ / 2.16 kg), with a dosage of 2.5 parts by weight; a heat stabilizer made of calcium-zinc composite stabilizer with a calcium-zinc molar ratio of 3:1, in powder form, with a dosage of 4 parts by weight; an auxiliary heat stabilizer made of epoxidized soybean oil with an epoxy value ≥6.0% and an acid value ≤0.5 mg KOH / g, with a dosage of 3 parts by weight; and an internal lubricant made of calcium stearate, industrial grade. The melting point is 155℃, and the dosage is 0.8 parts by weight; the external lubricant is polyethylene wax with a molecular weight of 2500 and a dropping point of 105℃, and the dosage is 0.4 parts by weight, with a weight ratio of 2:1, and a total dosage of 1.2 parts by weight; the inorganic filler is organic montmorillonite modified with hexadecyltrimethylammonium, with an interlayer spacing of 2.8nm, and the dosage is 1.5 parts by weight; the halogen-free flame retardant is a combination of zinc borate and magnesium hydroxide, with a weight ratio of 1:2, and a total dosage of 10 parts by weight; no traditional small molecule plasticizers are used.
[0070] The preparation process steps are as follows:
[0071] The first step is the premixing process. An SHR-200L high-speed mixer with a volume of 200L, variable frequency speed control, jacket electric heating, and water cooling is used. The hot mixing stage begins with the following: 100 parts by weight of polyvinyl chloride resin, 4 parts by weight of calcium-zinc composite stabilizer, 0.8 parts by weight of calcium stearate, 0.4 parts by weight of polyethylene wax, and 3 parts by weight of epoxidized soybean oil are weighed according to the formula and added sequentially to the high-speed mixer. The mixer is started, and the speed is set to 1200 rpm. The jacket is steam-heated until the material temperature reaches 110-115℃, and the hot mixing time is 7 minutes, allowing the stabilizer and lubricant to fully adsorb onto the surface of the PVC particles. The cold mixing stage then begins: heating is stopped, and the jacket circulating cooling water is switched to an inlet water temperature of 20℃, with the speed reduced to 800 rpm. When the material temperature drops to 85-90℃, 2.5 parts by weight of maleic anhydride-grafted acrylate copolymer, 1.5 parts by weight of organo-modified montmorillonite, 3.3 parts by weight of zinc borate, and 6.7 parts by weight of magnesium hydroxide are added. Continue cold mixing until the material temperature drops below 45°C before discharging. Install a 40-mesh sieve at the discharge port to obtain the PVC premix. Separately, take 12 parts by weight of polypropylene carbonate, 6 parts by weight of polyethylene carbonate, and 18 parts by weight of polypropylene carbonate copolymer. Dry mix them at room temperature for 5 minutes at 200 rpm in another low-speed mixer to obtain carbon dioxide-based polycarbonate masterbatch. Combine the above PVC premix and carbon dioxide-based polycarbonate masterbatch, and dry mix them at 800 rpm for 3 minutes in a high-speed mixer to obtain the final mixture. The final mixture should not be stored for more than 4 hours to avoid moisture absorption.
[0072] The second step is the melt blending and granulation process. An SHJ-36 co-rotating parallel twin-screw extruder with a screw diameter of 36mm and an L / D ratio of 44:1 is used, equipped with a vacuum exhaust port and a water bath pelletizing system. The screw configuration is the same as in Example 5. The temperature settings for each zone of the twin screw are as follows: Zone 1 (feeding section) 160℃, Zone 2 168℃, Zone 3 178℃, Zone 4 186℃, Zone 5 188℃, Zone 6 188℃, Zone 7 186℃, Zone 8 (vacuum port) 182℃, Zone 9 183℃, Zone 10 182℃, Zone 11 180℃, Zone 12 178℃, die head and dies head 184℃, with a maximum temperature of 188℃ throughout the process. The process parameters are set as follows: main engine speed 240 rpm; feeding frequency 28 Hz, corresponding to an output of approximately 20 kg / h; torque maintained at 65%~75%, current 22A~25A; melt pressure 5.5MPa~6.5MPa; vacuum degree -0.075MPa; material residence time in the screw 3.5 min. The total mixture is fed into the twin-screw extruder via a feeder. The material sequentially undergoes conveying, melting, shearing dispersion, vacuum devolatilization, and homogenization before being extruded from the die head. The extruded molten strip is cooled in a water bath at a temperature of 25℃~30℃, with a water tank length of 4m and a traction speed of 11m / min. It then enters a gantry pelletizer to be cut into pellets of 3mm~4mm in length. After being dehydrated in a centrifugal dryer for 30s, the pellets are sent to a fluidized bed dryer and dried with hot air at 60℃ until the moisture content is ≤0.08%. The final product is carbon dioxide-based polycarbonate modified PVC alloy granules, which are sealed in aluminum foil composite bags, protected with nitrogen, and stored at room temperature.
[0073] The alloy granules obtained in this embodiment were subjected to performance tests, and the results are as follows: the Vicat softening temperature (B50 method) is 89℃, and the notched impact strength (23℃) is 8.3kJ / m. 2 The tensile strength was 47 MPa, the elongation at break was 105%, the limiting oxygen index was 32%, the plasticizer migration rate (70℃×24h, filter paper pressing method) was 0.4 wt%, the melt flow rate (190℃ / 2.16kg) was 2.8 g / 10 min, and the Congo red test paper method (190℃×5 min) showed no color change and no HCl release.
[0074] Comparative Example 1
[0075] This comparative example uses a traditional PVC plasticizer with the following formulation: Based on 100 parts by weight of polyvinyl chloride resin, a general-purpose suspension SG-5 polyvinyl chloride resin with a degree of polymerization of 1000 and a K value of 65 is selected. No carbon dioxide-based polycarbonate components are added. The additives include: a calcium-zinc composite stabilizer with a calcium-zinc molar ratio of 3:1, in powder form, at a dosage of 4.5 parts by weight; an auxiliary heat stabilizer of epoxidized soybean oil with an epoxy value ≥6.0% and an acid value ≤0.5 mgKOH / g, at a dosage of 3.0 parts by weight; an internal lubricant of calcium stearate, industrial grade, with a melting point of 155℃, at a dosage of 0.6 parts by weight; an external lubricant of polyethylene wax with a molecular weight of 2500 and a dropping point of 105℃, at a dosage of 0.6 parts by weight; and a plasticizer of dioctyl phthalate (DOP), industrial grade, with a purity ≥99%, at a dosage of 45 parts by weight, which is the standard dosage for traditional PVC flexible products.
[0076] The preparation process steps are as follows:
[0077] The first step is the premixing process. An SHR-200L high-speed mixer with a volume of 200L, variable frequency speed control, jacketed electric heating, and water cooling is used. The hot mixing stage begins with the following: 100 parts by weight of polyvinyl chloride resin, 4.5 parts by weight of calcium-zinc composite stabilizer, 0.6 parts by weight of calcium stearate, 0.6 parts by weight of polyethylene wax, and 3.0 parts by weight of epoxidized soybean oil are weighed according to the formula and added sequentially to the high-speed mixer. The mixer is started, and the speed is set to 1200 rpm. The jacket is heated with steam until the material temperature reaches 110-115℃, and the hot mixing time is 7 minutes. The cold mixing stage then begins: heating is stopped, and the jacket circulating cooling water is switched to an inlet water temperature of 20℃. The speed is reduced to 800 rpm. When the material temperature drops to 85-90℃, 45 parts by weight of dioctyl phthalate are added. Cold mixing continues until the material temperature drops below 45℃ before discharge. A 40-mesh sieve is installed at the discharge port to obtain the PVC premix.
[0078] The second step is the melt blending and granulation process. An SHJ-36 co-rotating parallel twin-screw extruder is used, with a screw diameter of 36mm and a length-to-diameter ratio (L / D) of 44:1. It is equipped with a vacuum exhaust port and a water bath pelletizing system. The temperature settings for each zone of the twin screw are as follows: Zone 1 (feeding section) 160℃, Zone 2 168℃, Zone 3 178℃, Zone 4 186℃, Zone 5 188℃, Zone 6 188℃, Zone 7 186℃, Zone 8 (vacuum port) 182℃, Zone 9 183℃, Zone 10 182℃, Zone 11 180℃, Zone 12 178℃, and die head and end cap 184℃. The process parameters are set as follows: main extruder speed 220rpm, feeding frequency 28Hz, torque maintained at 55%~65%, melt pressure 4~5MPa, vacuum degree -0.07MPa, and material residence time in the screw 4min. The total mixture is fed into a twin-screw extruder via a feeder. The extruded molten strip is cooled in a water bath at a temperature of 25-30℃ (4m long, traction speed 10m / min), and then cut into pellets of 3mm-4mm length by a gantry pelletizer. After being dehydrated in a centrifugal dryer for 30s, the pellets are sent to a fluidized bed dryer and dried with hot air at 60℃ until the moisture content is ≤0.08%.
[0079] The performance of the granules obtained in this comparative example was tested, and the results are as follows: Vicat softening temperature (B50 method) was 68℃, and notched impact strength (23℃) was 4.2kJ / m. 2 The tensile strength was 32 MPa, the elongation at break was 180%, the limiting oxygen index was 24%, the plasticizer migration rate (70℃×24h, filter paper pressing method) was 4.8 wt%, the melt flow rate (190℃ / 2.16kg) was 8.5 g / 10 min, and the Congo red test paper method (190℃×5 min) showed slight discoloration and trace amounts of HCl release.
[0080] In this comparative example, the amount of DOP was as high as 45 parts by weight. Compared with Examples 1-7, its Vicat softening temperature was only 68°C, far lower than the 82°C-90°C of the alloy of this invention; the notched impact strength was only 4.2 kJ / m. 2 It is less than half the size of the alloy of this invention; the limiting oxygen index is only 24%, which is flammable; the plasticizer migration rate is as high as 4.8 wt%, which is 6 to 16 times that of the white alloy of this invention.
[0081] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention in any other way. Any person skilled in the art may make changes or modifications to the above-disclosed technical content to create equivalent embodiments. However, any simple modifications, equivalent changes, and modifications made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the protection scope of the present invention.
Claims
1. A carbon dioxide-based polycarbonate-modified PVC alloy, characterized in that, It is made by blending raw materials including the following components: 100 parts by weight of polyvinyl chloride resin; 10-160 parts by weight of carbon dioxide-based polycarbonate, wherein the carbon dioxide-based polycarbonate is selected from one or more of polypropylene carbonate, polyvinyl carbonate, and polypropylene carbonate copolymers, and the number average molecular weight is 2 × 10⁻⁶. 4 ~1×10 6 ; 0-30 parts by weight of additives; The melting and blending temperature of the alloy is 160℃~190℃.
2. The carbon dioxide-based polycarbonate-modified PVC alloy according to claim 1, characterized in that, The polypropylene carbonate is a binary copolymer of carbon dioxide and propylene oxide; the polyethylene carbonate is a binary copolymer of carbon dioxide and ethylene oxide; the polypropylene carbonate copolymer is a terpolymer of carbon dioxide, propylene oxide and phthalic anhydride.
3. The carbon dioxide-based polycarbonate-modified PVC alloy according to claim 1, characterized in that, The carbon dioxide-based polycarbonate is a combination of polypropylene carbonate and polypropylene carbonate copolymer, with a weight ratio of 1:0.3~2.
4. The carbon dioxide-based polycarbonate-modified PVC alloy according to claim 1, characterized in that, The carbon dioxide-based polycarbonate is a combination of polyvinyl carbonate and polypropylene carbonate copolymer, with a weight ratio of 1:0.5~3.
5. The carbon dioxide-based polycarbonate-modified PVC alloy according to claim 1, characterized in that, The carbon dioxide-based polycarbonate is a combination of polypropylene carbonate, polyvinyl carbonate and polypropylene carbonate copolymer, with a weight ratio of 1:0.2~0.8:0.5~2.
6. The carbon dioxide-based polycarbonate-modified PVC alloy according to claim 1, characterized in that, The additives include one or more of the following: compatibilizers, heat stabilizers, lubricants, plasticizers, inorganic fillers, and halogen-free flame retardants.
7. The carbon dioxide-based polycarbonate-modified PVC alloy according to claim 6, characterized in that, The compatibilizer is a maleic anhydride-grafted acrylate copolymer with a grafting rate of 0.5wt% to 2.0wt% and an amount of 0 to 5 parts by weight.
8. The carbon dioxide-based polycarbonate-modified PVC alloy according to claim 6, characterized in that, The heat stabilizer is a calcium-zinc composite stabilizer, with a calcium to zinc molar ratio of 2 to 4:1 and a dosage of 0 to 8 parts by weight.
9. A carbon dioxide-based polycarbonate-modified PVC alloy according to claim 6, characterized in that, The lubricant is a mixture of calcium stearate and polyethylene wax, with a weight ratio of 1:0.5~2, and a dosage of 0~3 parts by weight.
10. The carbon dioxide-based polycarbonate-modified PVC alloy according to claim 1, characterized in that, The polyvinyl chloride resin is a general-purpose suspension resin with a degree of polymerization of 800~1300 and a K value of 60~68.
